Social Values and Norms in the Mangalop Bona Unjuk Tradition at the Batak Simalungun Traditional Wedding Ceremony - Cristien Oktaviani Saragih; Basri Natan Sitanggang; Revi Angel Sonata Sitorus; Indah Sari; Flansius Tampubolon (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
The Batak Simalungun people have customs that are observed from conception to death, each with its own uniqueness and social values. This study aims to describe the social and ethical values ??in one of the Batak Simalungun traditional wedding processes, namely the Mangalop Bona Unjuk tradition, which is carried out before marriage by asking permission from an uncle or tondong. This tradition is not just a permission, but a form of respect and a manifestation of moral and social values passed down from generation to generation. This study uses a descriptive qualitative approach to explain the meaning of Mangalop Bona Unjuk, collecting data through case studies, including journals, books, and related websites. The results of the study show that this tradition embodies high social and ethical values such as respect, ethics, and family togetherness. In addition, Mangalop Bona Unjuk serves to strengthen kinship ties and secure the blessing of the extended family, ensuring the wedding process proceeds peacefully and joyfully. Thus, the Mangalop Bona Unjuk tradition plays an important role in shaping the character and maintaining the social balance of the Batak Simalungun people.